Characterization of Patients with Acinetobacter baumannii Ventilator-associated Pneumonia in Progressive Care Units - Leonardo Maikel Gómez Carcassés; Lester Pérez Hernández; Yeney Pujol Enseñat; Carmen Niurka Piña Loyola (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Background: Acinetobacter baumannii has become one of the most important nosocomial pathogens. Objective: to characterize the patients diagnosed with ventilator-associated pneumonia due to Acinetobacter baumannii in the Progressive Care Units. Methods: a case series study of patients diagnosed with ventilator-associated pneumonia due to Acinetobacter baumannii was conducted in the Progressive Care Units of the Dr. Gustavo Aldereguía Lima Hospital of Cienfuegos from December 2013 through December 2014. The study variables included: age, sex, comorbid conditions, cause of admission, duration of ventilation, length of stay, antibiotic used, and status at discharge. Results: a total of 39 patients were studied, which accounted for 69.2% of the patients in Progressive Care Units. The mean age was 55.7 years. Males predominated. Sixty four point two percent of patients reported one or more past illnesses. Most admissions to emergency services were due to clinical reasons (51.3%). Sixty nine point two percent of patients received mechanical ventilation for 3 to 21 days. The average stay was 14.7 days. Seventy one point eight percent received a combined antimicrobial treatment and most of them were discharged alive (64.1%). Overall mortality was 35.9%. Conclusions: there was a predominance of males, patients over 60 years of age and clinical cases. The study patients needed mechanical ventilation for a medium length of time and combined antimicrobial treatment. Most patients were discharged alive, and mortality was within the range of that reported in the scientific literature.